2018
DOI: 10.1590/1982-0224-20170157
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny and biogeographic history of the Neotropical tribe Glandulocaudini (Characiformes: Characidae: Stevardiinae)

Abstract: Although former studies on systematics and biogeography represent a progress on the knowledge of the tribe Glandulocaudini, none was grounded on molecular evidence. Thus, the first hypothesis of relationships for the tribe based on a multilocus analysis is presented, including all genera and most of the valid species. DNA sequences of Glandulocauda caerulea and Mimagoniates sylvicola were analyzed for the first time. A molecular clock analysis was used to estimate the origin of the Glandulocaudini and the appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(77 reference statements)
2
5
0
Order By: Relevance
“…Previous studies (Castro et al, 2003; Menezes & Weitzman, 2009) considered Lophiobrycon as sister group of a clade composed of Glandulocauda and Mimagoniates . Camelier et al (2018), in a phylogenetic study of the Glandulocaudini based on DNA/rRNA data, found that Glandulocauda was not monophyletic, since that study reconstructed Glandulocauda melanopleura (Ellis, 1911) as sister to Lophiobrycon weitzmani Castro et al, 2003 rather than being included in a clade with Glandulocauda caerulea Menezes & Weitzman, 2009, which turned out to be closely related to Mimagoniates . In our analysis, G. melanopleura and L. weitzmani are sister groups but we did not analyze G. caerulea .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (Castro et al, 2003; Menezes & Weitzman, 2009) considered Lophiobrycon as sister group of a clade composed of Glandulocauda and Mimagoniates . Camelier et al (2018), in a phylogenetic study of the Glandulocaudini based on DNA/rRNA data, found that Glandulocauda was not monophyletic, since that study reconstructed Glandulocauda melanopleura (Ellis, 1911) as sister to Lophiobrycon weitzmani Castro et al, 2003 rather than being included in a clade with Glandulocauda caerulea Menezes & Weitzman, 2009, which turned out to be closely related to Mimagoniates . In our analysis, G. melanopleura and L. weitzmani are sister groups but we did not analyze G. caerulea .…”
Section: Discussionmentioning
confidence: 99%
“…study, the monophyletic condition of the Glandulocaudini as proposed byThomaz et al (2015) is corroborated, including Mimagoniates as the sister group of Glandulocauda and Lophiobrycon. Previous studies(Castro et al, 2003;Menezes & Weitzman, 2009) considered Lophiobrycon as sister group of a clade composed of Glandulocauda and Mimagoniates Camelier et al (2018),. in a phylogenetic study of the Glandulocaudini based on DNA/rRNA data, found that Glandulocauda was not monophyletic, since that study reconstructed Glandulocauda melanopleura(Ellis, 1911) as sister to Lophiobrycon weitzmaniCastro et al, 2003 rather than being included in a clade with Glandulocauda caeruleaF I G U R E 9 Caudal-fin squamation of Knodus meridae, USNM 121469, 21.0 mm SL, lateral view, anterior to left.…”
mentioning
confidence: 99%
“…In addition, for Bryconamericus , one species boundary corresponds to the southern division inferred in our study (Hirschmann, Fagundes, & Malabarba, ); however, we note the lack of a correspondence between the designation of two other species within this taxon and the regional structure inferred here (i.e., north clusters: populations 40 and 41 for B. ornaticeps and population 42 for B. tenuis – see Supporting Information ), which results in a paraphyletic species under the currently proposed nomenclature. It is also notable that the old divergences associated with the central division are not correlated with any obvious morphological differentiation (Bertaco & Malabarba, ; Camelier, Menezes, Costa‐Silva, & Oliveira, ). The variation observed among taxa and geographic divisions could be viewed as evidence of divergence along a speciation continuum, where differentiation might be observed in a limited set of characters in some cases or across multiple traits, as expected as isolation persists (see Huang & Knowles, ).…”
Section: Discussionmentioning
confidence: 99%
“…Two main biogeographic processes explain events of geodispersal along the coastal rivers of southeastern Brazil: (a) headwater capture, a geomorphological process by which the river flow is diverted into the neighbouring basin (Bishop, 1995;Ribeiro, 2006;Roxo et al, 2014), and (b) Pleistocene paleodrainages, connections among coastal river systems during periods of marine regression (Dias et al, 2014;Thomaz et al, 2015;Thomaz & Knowles, 2018). Faunal interchanges because of headwater captures in southeastern Brazil have often been reported for several clades of Neotropical freshwater fishes (Camelier et al, 2018;Ribeiro, 2006) including loricariids (Lima et al, 2017;Roxo et al, 2014). The phylogeographic pattern observed in the loricariid Pareiorhaphis garbei is explained by headwater captures between the São João basin and the rivers draining the Guanabara Bay in RJ (Lima et al, 2017).…”
Section: Morphological Analysismentioning
confidence: 99%
“…Those molecular studies along with time-calibrated phylogenies have been used as a framework for biogeographic assumptions for coastal and inland loricariid taxa across the Serra do Mar mountain range in the Atlantic coast of Brazil (Roxo et al, 2014(Roxo et al, , 2019. Headwater captures and connections on the exposed continental shelf during sea-level fluctuations represent two frequently reported hypotheses explaining species diversification in that region (Albert & Reis, 2011;Ribeiro, 2006;Roxo et al, 2014;Thomaz & Knowles, 2018) that are supported by phylogeographic studies with freshwater fishes (Angrizani & Malabarba, 2018;Camelier et al, 2018;Lima et al, 2017;Thomaz et al, 2015;Wendt et al, 2019). Because of species endemicity and restricted distribution to the drainages of the Brazilian Shield, Kronichthys represents another model to study biogeographic processes underlying species diversification in the Serra do Mar mountain range.…”
mentioning
confidence: 97%